IMPLEMENTASI KURIKULUM BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING, ART AND MATH (STEAM) DALAM PEMBELAJARAN FIQIH: STUDI KASUS DI RAHMATAL LIL ‘ALAMIN INTERNATIONAL ISLAMIC BOARDING SCHOOL KABUPATEN SOLOK - Caniago, Faisal; Erawadi, Erawadi; Zulhammi, Zulhammi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Technological developments in the digital era require educational institutions, including Islamic boarding schools, to transform to remain relevant without losing their Islamic identity. This study aims to analyze in depth the design, implementation, and implications of the international Islamic boarding school curriculum based on Science, Technology, Engineering, Art, and Math (STEAM) at Rahmatan Lil 'Alamin International Islamic Boarding School (RLA IIBS) Solok, as well as to formulate a conceptual model design (alternative) for STEAM integration specifically in Fiqh learning. This research is a qualitative study with a case study approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The collected data were analyzed qualitatively (data condensation, data presentation, and drawing conclusions) and then synthesized into an alternative model design. The results of the study indicate that: (1) The design and implementation of the STEAM curriculum at RLA IIBS have been carried out as an adaptive response to the challenges of the digital era, but technical obstacles are still encountered in its complete integration into the religious sciences cluster; (2) Based on field findings and needs analysis, this study produces outputs in the form of a conceptual model design for the integration of Fiqh and STEAM. This alternative model was designed to improve the implementation of the Islamic boarding school curriculum so that it is more comprehensive, so that students not only master the latest science and technology, but also still have a deep understanding of religion (tafaqquh fiddin).